Intensification of convective heat exchange of walls of heat pipe of 3D-printed micro-sized turbojet engine - A. V. Pobelyansky; D. K. Dmitriev; A. A. Levikhin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article considers the solution of the urgent problem of creating a micro-sized turbojet engine using 3D printing. The article describes one of the ways to cool the walls of the heat pipe of a small combustion chamber made of heat-resistant material 08KhN53BMTYu. One of the acceptable ways to cool the walls of a small-sized chamber heat pipe is convective heat exchange of the outer side of the heat pipe due to intense vortex formation in the boundary layer of the flow. This effect is achieved by the device of projections on the outer wall of the heat pipe. The article highlights the peculiarity of the shape of the protrusions, which must be carried out taking into account the technological limitations of 3D printing. The article presents a description of an experimental stand for the study of the thermal state of the heat pipe of micro turbojet engines, the method of processing experimental data and the results of experiments on the heat transfer of the heat pipe shell with and without them.